Respiratory syncytial virus fusion glycoprotein: nucleotide sequence of mRNA, identification of cleavage activation site and amino acid sequence of N-terminus of F1 subunit. - Elango, N (1985)
The amino acid sequence of respiratory syncytial virus fusion protein (Fo) was deduced from the sequence of a partial cDNA clone of mRNA and from the 5' mRNA sequence obtained by primer extension and dideoxysequencing. The encoded protein of 574 amino acids is extremely hydrophobic and has a molecular weight of 63371 daltons. The site of proteolytic cleavage within this protein was accurately mapped by determining a partial amino acid sequence of the N-terminus of the larger subunit (F1) purified by radioimmunoprecipitation using monoclonal antibodies. Alignment of the N-terminus of the F1 subunit within the deduced amino acid sequence of Fo permitted us to identify a sequence of lys-lys-arg-lys-arg-arg at the C-terminus of the smaller N-terminal F2 subunit that appears to represent the cleavage/activation domain. Five potential sites of glycosylation, four within the F2 subunit, were also identified. Three extremely hydrophobic domains are present in the protein; a) the N-terminal signal sequence, b) the N-terminus of the F1 subunit that is analogous to the N-terminus of the paramyxovirus F1 subunit and the HA2 subunit of influenza virus hemagglutinin, and c) the putative membrane anchorage domain near the C-terminus of F1.